The Role of Antioxidants and Anti-Inflammatory Agents in Cardiometabolic Disease - Aryanugraha, Teguh; Sargowo, Djanggan; Rahimah, Anna Fuji; Tjahjono, Cholid Tri (Universitas Brawijaya, 2024)
Cardiovascular diseases remain a major cause of morbidity and mortality worldwide. Cardiovascular diseases associated with metabolic disorders are collectively referred to as Cardiometabolic Diseases (CMDs). Oxidative stress and inflammation are key contributors to the development and progression of CMDs. Antioxidants and anti-inflammatory agents have garnered significant attention as potential therapeutic strategies for preventing and managing cardiovascular disorders. To better understand the complex interactions between oxidative stress, inflammation, and cardiovascular health, this review paper will focus on the mechanisms of action and potential advantages of antioxidants and anti-inflammatory drugs in reducing the risk factors associated with CVDs and enhancing cardiovascular health in general.